COUNT KÁROLY KHUEN-HÉDERVÁRY AND THE SERBS IN HUNGARY AND CROATIA - Heka, Laszlo L. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Count Károly Khuen-Héderváry (1849th - 1918th); Hungarian politician and statesman, held the title of Viceroy of Croatia, Slavonia and Dalmatia from 1883th to 1903th, and was the President of the Hungarian Ministerial Council in two occasions (June 27th 1903 to November 3rd 1903 and January 17th 1910 to April 22nd 1912). Although he marked historical events at the turn of the 19th to the 20th century, in Yugoslav historiography and national consciousness he is remembered in an extremely negative context. It is interesting that on one hand he is generally known, but on the other hand we know very little about Count’s work, and that until today there hasn’t been written even one memoir about him, and there is a small amount of scientific paper about his political path. In this study we present the life and work of Károly Khuen-Héderváry as the Croatian Viceroy and the Hungarian Prime Minister and his attitude towards the National question, with special emphasis on cooperation with the Serbs in Hungary and Croatia. In fact, it was the Serbs who allowed him the twenty-year rule in Croatia, and in return Viceroy Khuen-Héderváry gave them very broad rights. This caused discontent of the Croats who, because of the relationship towards the Serbs, called him The Serbian Viceroy.